Implementasi Tahfidz dengan Metode Muri-Q di Madrasah Qur’aniyah Fastabiqul Khoirot Kendal - Adelia Cahya Rizki; Triono Ali Mustofa (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This research focuses on the implementation of tahfidz with the Muri-Q method in Madrasah Qur'aniyah Fastabiqul Khoirot Kendal, which combines rhythm and melody, is considered effective in making the memorization process more interesting and easy to understand. This study aims to find out how this method can improve the ability of students to memorize the Qur'an, as well as to identify the factors that support the successful application of the method. This study uses a descriptive qualitative approach. Data were collected through interviews, observations and documentation to obtain an in-depth picture of the application of the Muri-Q method. Data analysis was carried out to identify the factors that affect the success of this method. The results of the study show that the Muri-Q method has a positive impact on improving the memorization of the Qur'an in students. The use of audio-visual media such as Youtube and speakers is very helpful for students in understanding the tone of reading. There are six supporting factors: such as familiar methods, conducive learning environments, makharijul approach and tajweed law, division by age, superior programs, and the use of audio-visual media also contribute to the success of this method. The Muri-Q method has proven to be effective in improving the ability to memorize the Qur'an. This research suggests the need for further development in teaching methods to overcome existing challenges and improve the effectiveness of the Muri-Q method.